2013
DOI: 10.3382/ps.2012-02853
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary supplementation with the natural carotenoids curcumin and lutein on broiler pigmentation and immunity

Abstract: The objective of this study was to compare the effects of supplementation with 2 carotenoids, curcumin and lutein, on pigmentation and immunity in lipopolysaccharide (LPS)-stimulated broiler chicks. Two hundred forty 1-d-old Arbor Acres broilers were randomly distributed into 3 dietary treatment groups: a basal diet without carotenoid supplementation (control), a basal diet supplemented with 200 mg/kg of curcumin (CRM), or a basal diet supplemented with 200 mg/kg of lutein (LTN) for 42 d. The birds were vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 27 publications
5
50
0
3
Order By: Relevance
“…In the present study, we also found that the addition of marigold extract significantly increased the b* value of the thigh muscle and skin. This might be due to deposition of marigold extract pigments in the muscle and skin, and many previous studies have obtained similar results [1315]. Castaneda et al [4] also indicated that natural pigments were generally more effective than synthetic ones in improving the yellowness of animal skin.…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, we also found that the addition of marigold extract significantly increased the b* value of the thigh muscle and skin. This might be due to deposition of marigold extract pigments in the muscle and skin, and many previous studies have obtained similar results [1315]. Castaneda et al [4] also indicated that natural pigments were generally more effective than synthetic ones in improving the yellowness of animal skin.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, Pantoea-6 ® was made from extraction of fermented wheat flour with Pantoea agglomerans, which is gram-negative bacteria (Hebishima et al, 2010). Rajput et al (2013) reported that LPS is a structural component of the outer membrane of gram-negative bacteria. Xie et al (2000) found that LPS increased the total plasma protein concentration in chickens.…”
Section: General Remarksmentioning
confidence: 99%
“…Dietary lutein also induced both cell‐mediated and humoral immune responses (IgG) and enhanced the percentages of cells expressing CD5, CD4, CD8 and MHC II molecules in domestic canines (Kim et al ., ,b). Lutein‐supplemented birds showed superior efficiency of pigmentation as compared with curcumin‐supplemented birds; however, both groups of birds had reduced lipid oxidation in the liver (Rajput et al ., ). Lutein protected the retina from ischaemic/hypoxic damage by its anti‐oxidative, anti‐inflammatory and anti‐apoptotic activities (Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%